2010
DOI: 10.3390/ma3125054
|View full text |Cite
|
Sign up to set email alerts
|

Mn-doped Ge and Si: A Review of the Experimental Status

Abstract: Diluted ferromagnetic semiconductors (FMS) are in the focus of intense research due to their potential applications in spintronics and their striking new physical properties. So far Mn-doped III-V compound semiconductors such as GaMnAs are the most important and best understood ones, but they are ferromagnetic only at well below room temperature. An interesting alternative could be magnetic semiconductors based on elemental semiconductors, also owing to their compatibility with Si microelectronics. In the last… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 88 publications
0
16
1
1
Order By: Relevance
“…In particular, Mn doped Ge based diluted magnetic semiconductors (DMSs) exhibit specific magnetic and transport properties which allow them to be used for high-frequency applications. Recent studies on these materials have shown that the growth condition and magnetic impurity concentration play a significant role in determining the spatial distribution of magnetic dopants and their magnetic coupling [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, Mn doped Ge based diluted magnetic semiconductors (DMSs) exhibit specific magnetic and transport properties which allow them to be used for high-frequency applications. Recent studies on these materials have shown that the growth condition and magnetic impurity concentration play a significant role in determining the spatial distribution of magnetic dopants and their magnetic coupling [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, most of the studies of Si 1 À x Mn x system have been performed on the samples with relatively low content of manganese ions (xo 0.05) incorporated by ion-implantation (see [1][2][3][4] and references therein) and FM ordering above room temperature (RT) has been revealed. However, these dilute alloys turn out to be strongly inhomogeneous materials due to their phase segregation, with isolated magnetic MnSi 1.7 nanoparticles (х $ 0.35) precipitated in the Si matrix [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Si-Mn alloys attract an increasing interest for application in spintronic as integrated-circuit elements easily incorporated into the existing microelectron technology [1] and also exhibit unusual magnetic and transport behavior [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…• C as well as after magnetron cosputtering, showed evidence for the presence of Mn atoms on the substitutional lattice site, [17,18] pure Mn, after which a thermal treatment was given. This consisted of heating from room temperature to 700…”
Section: Introductionmentioning
confidence: 99%